The relationship between English listening proficiency levels and learning styles - Farinaz Shirani Bidabadi,; Hamidah Yamat, (Penerbit UKM, 2012)
Several factors have been investigated in order to understand how learners attempt to learn a second language, one of which is learning style. Learners particularly EFL learners from different English language backgrounds and listening proficiency may vary from one another in their learning style preferences. With such a view, it is essential to consider the differences in learning styles and listening proficiency levels in teaching because this would have an impact on the learning process. The aim of the study was to identify Iranian freshmen’s levels of English listening proficiency and their learning style preferences as well as the relationship between them. A group of 92 freshmen from a population of 120 freshmen were randomly selected from a university in Esfahan, Iran. The Oxford Placement Test was first administered to identify the freshmen’s listening proficiency levels and the learning style preferences. Questionnaire was employed to identify their preferred learning styles. Based on the results obtained from the Oxford Placement Test, 19 freshmen were identified as advanced learners, 39 intermediate learners, and 34 low proficiency learners. The descriptive analysis of the learning style preferences indicated that all the learners preferred high level learning styles and considered themselves as communicative learners. The Pearson Correlation analysis also indicated that there was a significant positive correlation between the learners’ English listening proficiency levels and their learning style preferences. The implication of the study is that all lecturers should be aware of their learners’ learning style preferences and their English listening proficiency levels in order to match their teaching styles with their learners’ learning style preferences.